A Highly Luminescent Tetrahydrocurcumin IrIII Complex with Remarkable Photoactivated Anticancer Activity. Issue 33 (13th May 2019) - Colombo, Alessia; Fontani, Mattia; Dragonetti, Claudia; Roberto, Dominique; Williams, J. A. Gareth; Scotto di Perrotolo, Rossella; Casagrande, Francesca; Barozzi, Sara; Polo, Simona
Abstract: Curcumin has chemopreventative properties against a variety of tumours, but has poor bioavailability. Here, two new bis‐cyclometallated iridium(III) complexes have been prepared, featuring the natural product curcumin (CUR) or its reduced form, tetrahydrocurcumin (THC), as bidentate, anionic O O ‐binding ligands. The iridium THC complex is highly luminescent in deoxygenated solution and efficiently generates singlet oxygen under aerated conditions, whereas in the CUR analogue, other non‐radiative decay pathways are competitive. The complexes are rapidly taken up by a variety of human tumour cell lines from solutions of micromolar concentration. They show negligible cytotoxicity in the absence of irradiation. When briefly irradiated with visible light, Ir‐THC becomes highly phototoxic, inducing rapid apoptosis within 2 h. The results show the high potential of such complexes as sensitizers in photodynamic therapy (PDT). Abstract : Photoactivated anticancer/imaging agent : A novel highly phosphorescent cyclometallated curcuminoid Ir III complex (see graphic), which easily enters into mitochondria, is highly phototoxic upon irradiation with suitable light, but not cytotoxic in the dark. It is an excellent tool for combined photodynamic therapy and cell imaging.